Blood contains circulating cell‐free respiratory competent mitochondria. Issue 3 (19th January 2020) - Al Amir Dache, Zahra; Otandault, Amaëlle; Tanos, Rita; Pastor, Brice; Meddeb, Romain; Sanchez, Cynthia; Arena, Giuseppe; Lasorsa, Laurence; Bennett, Andrew; Grange, Thierry; El Messaoudi, Safia; Mazard, Thibault; et al.
Abstract: Mitochondria are considered as the power‐generating units of the cell due to their key role in energy metabolism and cell signaling. However, mitochondrial components could be found in the extracellular space, as fragments or encapsulated in vesicles. In addition, this intact organelle has been recently reported to be released by platelets exclusively in specific conditions. Here, we demonstrate for the first time, that blood preparation with resting platelets, contains whole functional mitochondria in normal physiological state. Likewise, we show, that normal and tumor cultured cells are able to secrete their mitochondria. Using serial centrifugation or filtration followed by polymerase chain reaction‐based methods, and Whole Genome Sequencing, we detect extracellular full‐length mitochondrial DNA in particles over 0.22 µm holding specific mitochondrial membrane proteins. We identify these particles as intact cell‐free mitochondria using fluorescence‐activated cell sorting analysis, fluorescence microscopy, and transmission electron microscopy. Oxygen consumption analysis revealed that these mitochondria are respiratory competent . In view of previously described mitochondrial potential in intercellular transfer, this discovery could greatly widen the scope of cell‐cell communication biology . Further steps should be developed to investigate the potential role of mitochondria as a signaling organelle outside the cell and to determine whether these circulating units could be relevant for early detection and prognosis of various diseases.